A Comorbidity-based Screening Tool to Predict Severe Maternal Morbidity at the Time of Delivery. Issue 2 (June 2020) - Easter, S.R.; Bateman, B.T.; Sweeney, V.H.; Manganaro, K.; Lassey, S.C.; Gagne, J.J.; Robinson, J.N.
Abstract : ( Am J Obstet Gynecol . 2019;221:271.e1–271.e10) An important strategy for improving maternal health is development of a tool that reliably identifies women at risk of severe maternal morbidity (SMM) and death. The obstetric comorbidity index (OB-CMI) summarizes the burden of maternal comorbidities and allows for the generation of a single numeric score to quantify risk assessment. While the OB-CMI was originally designed to address bias in research studies, the authors hypothesized it could be adapted for clinical use. The score is calculated from a 20-item list of comorbidities (eg, preeclampsia, multiple gestation, asthma, advanced maternal age). The comorbidities are weighted (eg, preeclampsia with severe features is 5 points, diabetes on insulin is 1 point). The points are summed for a total score. The aim of this study was to prospectively evaluate the performance of this comorbidity index as a screening tool to accurately identify laboring women at risk of SMM.